Electrochemical and Quantum Chemical Assessment of 2-Aminothiazole as Inhibitor for Carton Steel in Sulfuric Acid Solution - Guo, Lei; Zhu, Shanhong; Li, Wenpo; Zhang, Shengtao (Asian Journal of Chemistry, 2015)
Inhibition action of 2-aminothiazole towards carton steel corrosion in 0.1 M H2SO4 solution was investigated by electrochemical measurements. Quantum chemical calculations based on the density functional theory were performed on 2-aminothiazole. The polarization measurements show that 2-aminothiazole is arranged as a mixed-type inhibitor for both anodic and cathodic reactions. The surface morphology of uninhibited and inhibited carton steel sample was examined by scanning electron microscope. Moreover, a low-coverage gas-phase adsorption of 2-aminothiazole on perfect Fe(110) surface has been studied and characterized using density functional theory calculations.